Ah Analisis Hambatan Belajar Siswa Kelas IV Pada Mata Pelajaran Matematika - Anisatul Hidayah; Maemonah Maemonah (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2022)
The purpose of this study was to determine the learning barriers experienced by students in learning mathematics subject matter of multiples and factors of a number. Learning difficulties experienced by students when in the learning process are caused by gaps or distances between expected academic achievement and actual academic achievement. This study uses descriptive qualitative research methods by using data collection techniques through interviews, observation, and documentation as well as using descriptive analysis methods. With class IV A participants totaling 27 students. The results showed that there were learning barriers experienced by Class IV A in mathematics subject matter of multiples and factors of a number. Forms of learning barriers include; 1) lack of readiness of students in learning; 2) difficulty in solving questions; 3) limited understanding of students' concepts. Based on the results of research conducted, learning barriers were found to be found in ontogeny barriers as many as 5 students, didactic barriers as many as 2 students, and epistemological barriers as many as 2 students. By knowing the learning barriers experienced by students in learning the teacher can minimize student learning barriers so that there is no gap between academic achievement and the academic achievement to be achieved. Keywords: Learning Barriers, Mathematics, and Elementary Schools.